Combined impact of land cover, precipitation, and catchment area on discharge and phosphorus in the Mississippi basin's subcatchments. Issue 1 (5th January 2021) - Allafta, Hadi; Opp, Christian; Kolli, Meena
Abstract: Phosphorus (P) supplies (concentrations and fluxes) are essential drivers for biological activities in rivers and should be controlled to prevent eutrophication that usually results from urbanization and agricultural expansion. In this study, data from 26 subcatchments in the Mississippi basin were compiled from 2013 to 2017 to identify how catchment area, precipitation, and land cover affect discharge and total P (TP) and how TP yield diverges from a generalized local response mode. Results revealed that area‐weighted discharge ( Q area ) is controlled by precipitation and land cover (i.e., increases with precipitation and with both urban and forestland covers and decreases with both shrub/scrub and pasture/grassland covers). Total P concentration increases with agricultural land cover and decreases with both forest and water/wetland covers. Total P yield ( Q area × concentration) is governed mainly by Q area because the latter changes by a higher order of magnitude compared with concentration in the current study. Hence, TP yield follows the same trends that Q area exhibits with precipitation and land cover. In all catchments, TP yield varied significantly ( p < .05) and positively with instantaneous discharge. However, the rate of yield variations with discharge exhibited a significant ( p < .0001) strong negative ( r 2 = −.74) correlation with catchment area. This study provided a robust model that can predict the TP concentration and yield across different catchment scales in the Mississippi basin by means of discharge readings. Core Ideas: Total phosphorus (TP) response to land cover and precipitation is defined. TP concentration is sensitive to land cover change. TP yield is governed by a coupling of precipitation with land cover. TP yield vs. discharge correlation (i.e., TP yield rate) is controlled by catchment area. TP concentration and yield are predicted based on measurements of discharge.